Molecular dynamics simulation study of carboxylated and sulfonated poly(arylene ether sulfone) membranes for fuel cell applications. (7th December 2015) - Khodaparast-Kazeroonian, Fatemeh; Amjad-Iranagh, Sepideh; Modarress, Hamid
Abstract: The performance of poly(arylene ether sulfone) as a proton exchange membrane, for application in a fuel cell, such as carboxylic acid side chain effects on the structural and dynamical properties have been studied by molecular dynamics simulation at 353 K. Different percentage of carboxylated monomer were simulated and the radial distribution function, water cluster size and mean square displacement were evaluated. The results showed that monomer carboxylation up to 10%, decreased the conductivity according to vehicular mechanism and then at 15% of monomer carboxylation the conductivity increased. Also, the greatest water clusters were formed at 15% carboxylated monomer and the increase in acidic sites made the polymer more hydrophilic. In addition, the diffusion and solubility of the gases, O2 and H2, into the membrane were studied and the results indicated that H2 has a higher diffusion coefficient than O2 and the diffusion phenomenon has a determining effect on the performance of proton exchange membrane. Highlights: Carboxylated polymer membranes used in fuel cell were studied by MD simulation. Carboxylation of poly(arylene ether sulfone) affected membrane properties. Water cluster formation was investigated in the fuel cell membranes. Membrane proton conductivity decreased by gas (H2 and O2 ) diffusion.